Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1991
DOI: 10.1093/oxfordjournals.jbchem.a123584
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Streptomyces Serine-Protease Inhibitors with Streptomyces griseus Metalloendopeptidase II

Abstract: Streptomyces griseus metalloendopeptidase II (SGMPII) was shown to form tight complexes with several Streptomyces protein inhibitors which had been believed to be specific to serine proteases, such as Streptomyces subtilisin inhibitor (SSI), plasminostreptin (PS), and alkaline protease inhibitor-2c' (API-2c'), as well as with Streptomyces metalloprotease inhibitor (SMPI). The dissociation constants of complexes between SGMPII and these inhibitors were successfully determined by using a novel fluorogenic bimane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 0 publications
2
12
0
Order By: Relevance
“…The removal of both amino acids resulted in full depletion of inhibitory activity. We assume that SSI and other SSI-like metalloprotease inhibitors such as SgiA use, alike SSTI, this inhibition site, despite the fact that the exchange of amino acids within the subtilisin binding loop may alter the dissociation constant by one order of magnitude [5]. Our conclusion was supported by former studies with SSI-like Streptomyces cinnamoneus subsp.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The removal of both amino acids resulted in full depletion of inhibitory activity. We assume that SSI and other SSI-like metalloprotease inhibitors such as SgiA use, alike SSTI, this inhibition site, despite the fact that the exchange of amino acids within the subtilisin binding loop may alter the dissociation constant by one order of magnitude [5]. Our conclusion was supported by former studies with SSI-like Streptomyces cinnamoneus subsp.…”
Section: Discussionsupporting
confidence: 81%
“…Moreover, SSI proteins strongly affect activity of the Streptomyces griseus metalloprotease II (SGMPII, SgmA, griselysin, http://www.uniprot.org/uniprot/B1W035/http://www.uniprot.org/uniprot/Q83WH1), which was thought to compete with subtilisin BPN’ for the same inhibition site . However, substitution or deletion of SSI‐Met104 and adjacent amino acids could not decisively break the inhibition of SGMPII, and dissociation constants were at most altered by one order of magnitude . In contrast, the Streptomyces caespitosus neutral protease inhibitor (ScNPI, http://www.uniprot.org/uniprot/Q9FDS0) for the metalloprotease ScNP (snapalysin, http://www.chem.qmul.ac.uk/iubmb/enzyme/EC3/4/24/77.html, http://www.uniprot.org/uniprot/P56406), originally obtained from the undefined Streptomyces isolate I‐355, was completely inactivated by the exchange of ScNPI‐Tyr61 for alanine that is located two residues downstream from the N‐terminal cysteine and opposite to the subtilisin‐affine methionine (ScNPI‐Met99) .…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it is interesting that a molecule structurally related to the inhibitors of one class of proteases (i.e., serine proteases) regulates a member of another class of proteases (i.e., MMPs). This is not, however, unprecedented: several serine protease inhibitors, including ␣-macroglobulins (34), the Streptomyces subtilisin family of inhibitors (35), and the amyloid precursor protein (36), have been reported to inhibit metalloproteinases. Further studies on the interaction between RECK and MMP-9 may yield new insights into how such cross-class proteaseprotease inhibitor interactions occur.…”
Section: Discussionmentioning
confidence: 99%
“…Each strain was grown on a plate containing 2% skim milk, 1% lactose, and 0.1% yeast extract at 37ЊC for 24 h. The temperature was then shifted to 25ЊC, and incubation was continued for 120 h. The assay plate was not supplemented [SSI(Ϫ)] or was supplemented [1 g/ml of medium; SSI(ϩ)] with SSI. (11,40) have demonstrated that the metalloproteases SGMPI and SGMPII, isolated from pronase P of S. griseus, are strongly inhibited by serine protease inhibitors such as SSI, alkaline protease inhibitor (API-2cЈ) (29), and plasminostreptin (12) as well as a metalloprotease inhibitor (SMPI from Streptomyces nigrescens TK-24) (20). Therefore, grouping of proteases and their inhibitors on the basis of their individual genus or species specificities should also be considered from the viewpoint of their physiological functions.…”
Section: Discussionmentioning
confidence: 99%